Deficiency of ATP-Binding Cassette Transporters A1 and G1 in Macrophages Increases Inflammation and Accelerates Atherosclerosis in Mice - Westerterp, Marit; Murphy, Andrew J.; Wang, Mi; Pagler, Tamara A.; Vengrenyuk, Yuliya; Kappus, Mojdeh S.; Gorman, Darren J.; Nagareddy, Prabhakara R.; Zhu, Xuewei; Abramowicz, Sandra; Parks, John S.; Welch, Carrie; et al. (Circulation research, 2013)
RATIONALE:Plasma high-density lipoprotein levels are inversely correlated with atherosclerosis. Although it is widely assumed that this is attributable to the ability of high-density lipoprotein to promote cholesterol efflux from macrophage foam cells, direct experimental support for this hypothesis is lacking. OBJECTIVE:To assess the role of macrophage cholesterol efflux pathways in atherogenesis. METHODS AND RESULTS:We developed mice with efficient deletion of the ATP-binding cassette transporters A1 and G1 (ABCA1 and ABCG1) in macrophages (MAC-ABC mice) but not in hematopoietic stem or progenitor populations. MAC-ABC bone marrow (BM) was transplanted into Ldlr recipients. On the chow diet, these mice had similar plasma cholesterol and blood monocyte levels but increased atherosclerosis compared with controls. On the Western-type diet, MAC-ABC BM–transplanted Ldlr mice had disproportionate atherosclerosis, considering they also had lower very low-density lipoprotein/low-density lipoprotein cholesterol levels than controls. ABCA1/G1-deficient macrophages in lesions showed increased inflammatory gene expression. Unexpectedly, Western-type diet–fed MAC-ABC BM–transplanted Ldlr mice displayed monocytosis and neutrophilia in the absence of hematopoietic stem and multipotential progenitor cells proliferation. Mechanistic studies revealed increased expressions of machrophage colony stimulating factor and granulocyte colony stimulating factor in splenic macrophage foam cells, driving BM monocyte and neutrophil production. CONCLUSIONS:These studies show that macrophage deficiency of ABCA1/G1 is proatherogenic likely by promoting plaque inflammation and uncover a novel positive feedback loop in which cholesterol-laden splenic macrophages signal BM progenitors to produce monocytes, with suppression by macrophage cholesterol efflux pathways.